The Effect of Corporate Social Responsibility and Leverage on Firm Value with Profitability as a Moderating Variable - Salsabila; Dara Ayu Nianty; Mutiarini Mubyl (Jurnal Informatika Ekonomi Bisnis, 2026)
This study aims to analyze the effect of Corporate Social Responsibility and leverage on firm value, with profitability as a moderating variable, in coal mining subsector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. This study is motivated by the phenomenon of weak firm value in the coal mining sector and the inconsistency of previous research results regarding the influence of CSR, leverage, and profitability on firm value. This study uses Signaling Theory as a theoretical basis to explain the relationship between the research variables. The research method used is a quantitative approach using secondary data in the form of financial reports and company annual reports. The sampling technique used a purposive sampling method, resulting in 18 companies as research samples with a total of 90 observations during the study period. Data analysis techniques used include descriptive statistical analysis, classical assumption tests, multiple linear regression analysis, and Moderated Regression Analysis. The results show that Corporate Social Responsibility has a significant negative effect on firm value. Leverage does not have a significant effect on firm value. Profitability is unable to moderate the effect of CSR on firm value. However, profitability is able to moderate and strengthen the effect of leverage on firm value. The results of this study indicate that investors in the coal mining sector tend to consider a company's ability to generate profits and manage its funding structure more than CSR when assessing a company.